African Americans’ views on research and the Tuskegee Syphilis study - Freimuth, Vicki S; Quinn, Sandra Crouse; Thomas, Stephen B; Cole, Galen; Zook, Eric; Duncan, Ted (Social science & medicine (1982), 2001)
The participation of African Americans in clinical and public health research is essential. However, for a multitude of reasons, participation is low in many research studies. This article reviews the literature that substantiates barriers to participation and the legacy of past abuses of human subjects through research. The article then reports the results of seven focus groups with 60 African Americans in Los Angeles, Chicago, Washington, DC, and Atlanta during the winter of 1997. In order to improve recruitment and retention in research, the focus group study examined knowledge of and attitudes toward medical research, knowledge of the Tuskegee Syphilis Study, and reactions to the Home Box Office production, Miss Evers’ Boys, a fictionalized version of the Tuskegee Study, that premiered in February, 1997. The study found that accurate knowledge about research was limited; lack of understanding and trust of informed consent procedures was problematic; and distrust of researchers posed a substantial barrier to recruitment. Additionally, the study found that, in general, participants believed that research was important, but they clearly distinguished between types of research they would be willing to consider participating in and their motivations for doing so.